Aperture antenna embedded notched parallel plate waveguide and its application to dual-polarized 3-D absorptive frequency-selective transmission structure - Zhang, Binchao (2021)
This paper introduces an angular-insensitive dual-polarized 3-D absorptive frequency-selective transmission structure (AFST), which has a transmission window and an upper absorption band. The transmission band is produced by lossless resonators implemented using an aperture antenna embedded notched parallel plate waveguide with a metalized via hole in the center. The absorption band is obtained by lossy resonators constructed by the single resistor embedded bent metallic strips. In addition, the whole structure is constructed without backing discontinuous metallic ground plane, which overcomes the fabrication difficulty of conventional 3-D structures. Physical mechanism of the proposed AFST is explained with the aid of an equivalent circuit model, as well as current and electric field distributions. A prototype of the designed AFST is fabricated and measured, and experimental results show that a fractional transmission bandwidth of 20.5% and an upper absorption bandwidth of 28.8% with absorptivity around 90% for both TE- and TM-polarizations are achieved under oblique incident wave up to 50°.